2006
DOI: 10.1177/0361198106198200104
|View full text |Cite
|
Sign up to set email alerts
|

Another Look at Pedestrian Walking Speed

Abstract: Pedestrians have a wide range of needs and abilities. FHWA's Manual on Uniform Traffic Control Devices for Streets and Highways includes a walking speed of 4.0 ft/s (1.2 m/s) for calculating pedestrian clearance intervals for traffic signals. It also includes a comment that where pedestrians who walk slower than normal, or pedestrians who use wheelchairs, routinely use the crosswalk, a walking speed of less than 4.0 ft/s should be considered in determining the pedestrian clearance times. A 2005 TCRP-NCHRP stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 4 publications
9
62
3
Order By: Relevance
“…Overall, the speed threshold (i.e., the fastest pace that the user can walk without causing system localization failures) was found to be around 6.4 km/h to 7.6 km/h. Previous studies found that the general walking speed is around 3.4 km/h to 5.5 km/h [36], which is below the threshold speed. As a result, we could expect our system to be feasible for practical use at normal walking speed.…”
Section: Technical Assessment Results and Discussionmentioning
confidence: 82%
“…Overall, the speed threshold (i.e., the fastest pace that the user can walk without causing system localization failures) was found to be around 6.4 km/h to 7.6 km/h. Previous studies found that the general walking speed is around 3.4 km/h to 5.5 km/h [36], which is below the threshold speed. As a result, we could expect our system to be feasible for practical use at normal walking speed.…”
Section: Technical Assessment Results and Discussionmentioning
confidence: 82%
“…To further understand the role of user speed, we examined the distribution of user speeds for both alcoholic and nonalcoholic user-nights. A participant was considered stationary if the computed speed was below 1 km/h, while a participant was assumed to be walking if the speed was in the range of 2-5 km/h [49]. In Figure 7, we show the percentage of time (as a fraction of a user night) when the user was stationary or walking for both night types.…”
Section: Resultsmentioning
confidence: 99%
“…For instance Indians maintain higher speeds and less headways when compared to Germans [45]. From the previous studies, [49][50][51][52][53] it is evident that younger pedestrians maintain higher speeds when compared to old pedestrians. Also men walk at higher speeds while compared to women [17,[49][50][51][52][53][54][55].…”
Section: Walking Speeds At Various Facilitiesmentioning
confidence: 99%
“…From the previous studies, [49][50][51][52][53] it is evident that younger pedestrians maintain higher speeds when compared to old pedestrians. Also men walk at higher speeds while compared to women [17,[49][50][51][52][53][54][55]. Tanaboriboon et al [49] reported the mean walking speed in Singapore as 74 m/min which is relatively slower than the walking speeds in American counterparts.…”
Section: Walking Speeds At Various Facilitiesmentioning
confidence: 99%